AS ADVERSIDADES ATUAIS DO DIREITO PREVIDENCIARIO ALINHADO AO SEGURADO ESPECIAL (REMUNOM, 2024)
Social Security is the cornerstone of any society's social security system and provides financial protection and assistance to citizens during vulnerable periods, such as retirement, disability or death. Focusing on this statement, this article deals with the relevant topic of the current difficulties of Social Security Law with special insured people, in this context the special insurer becomes a very important figure. However, we can emphasize the importance of the social security rights of special insured persons, addressing the obstacles to informality in the presentation of documentary evidence and, therefore, the need to make the requirement for this proof more flexible. Likewise, the importance of social security for special insured people stands out, which is useful for Brazilian society. Starting from this point of view, the objective of this work is to propose a more comprehensive analysis of the problems, understand their causes and consequences and explore possible strategies to guarantee full access to social security for those with special insurance. In this sense, it is important to emphasize the importance of the social security rights of special insured persons and seek solutions to remove the obstacles that prevent their realization. In doing so, we not only promote social justice and protect the human rights of these workers, but we also help strengthen the entire Brazilian pension system. Methods: Demonstrate the social difficulties faced by special insured people in proving their agricultural status for retirement purposes, as physical evidence is often insufficient to prove their status as special insured. The main objective of this article is to show the obstacles to the implementation of the social security rights of special insured individuals.